Looking Beyond ‘White Slavery’: Trafficking, the Jewish Association, and the dangerous politics of migration control in England, 1890-1910 - Attwood, Rachael (Anti-Trafficking Review, 2016)
This article seeks to revise Jo Doezema’s suggestion that ‘the white slave’ was the only dominant representation of ‘the trafficked woman’ used by early anti-trafficking advocates in Europe and the United States, and that discourses based on this figure of injured innocence are the only historical discourses that are able to shine light on contemporary anti-trafficking rhetoric. ‘The trafficked woman’ was a figure painted using many shades of grey in the past, with a number of injurious consequences, not only for trafficked persons but also for female labour migrants and migrant populations at large. In England, dominant organisational portrayals of ‘the trafficked woman’ had acquired these shades by the 1890s, when trafficking started to proliferate amid mass migration from Continental Europe, and when controversy began to mount over the migration of various groups of working-class foreigners to the country. This article demonstrates these points by exploring the way in which the Jewish Association for the Protection of Girls and Women (JAPGW), one of the pillars of England’s early anti-trafficking movement, represented the female Jewish migrants it deemed at risk of being trafficked into sex work between 1890 and 1910. It argues that the JAPGW stigmatised these women, placing most of the blame for trafficking upon them and positioning them to a greater or a lesser extent as ‘undesirable and undeserving working-class foreigners’ who could never become respectable English women. It also contends that the JAPGW, in outlining what was wrong with certain female migrants, drew a line between ‘the migrant’ and respectable English society at large, and paradoxically endorsed the extension of the very ‘anti-alienist’ and Antisemitic prejudices that it strove to dispel.